The influence of ideological entrepreneurship to social enterprise's success. (March 2018) - Permana, A; Mursitama, T N
Abstract: Corporate Social Responsibility (CSR) activities are often a product of the tension between a company's function as a profit-optimizing institution and its social obligations, which are grounded in particular locus of sociality, which bring about change in the local society. There is also a global push to consider environmental factors and the sustainable development. The successful implementation of CSR activities of PT. Riau Andalan Pulp and Paper (RAPP) in Riau, Indonesia, is an example of a program based on business and ethical values. This case produced successful models for the CSR-based social enterprise. The hypothesis here is that the success of a social enterprise is due in part to underlying moral philosophy, such as how ideological entrepreneurship is implemented based on ideological, personal and local values. Without neglecting the search for the essence of business operations, which give space for community development and empowerment, this research also proves the influence of ideological entrepreneurship on the success of a social enterprise.